2024
DOI: 10.3390/ijms25010567
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Composition and Dynamics in Hospitalized COVID-19 Patients and Patients with Post-Acute COVID-19 Syndrome

Monta Brīvība,
Laila Silamiķele,
Līga Birzniece
et al.

Abstract: The gut microbiome plays a pivotal role in the modulation of host responses during viral infections, and recent studies have underscored its significance in the context of coronavirus disease 2019 (COVID-19). We aimed to investigate the dynamics and compositional changes in the gut microbiome of COVID-19 patients, addressing both the acute phase and the recovery process, with a particular focus on the emergence of post-COVID-19 conditions. Involving 146 COVID-19 patients and 110 healthy controls, this study em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Distinct microbial signatures were identified, with the prevalence of specific OTUs in COVID-19 patients and a particular abundance of Prevotella in severe cases. This was similar to findings from a recent study [30] which highlighted a protective role of the Prevotella genus in the long-term recovery process while other investigations [31,32] reported varied results. The variation could be attributed to various factors like sample collection methods, patient demographics, or even geographic variations in microbial populations.…”
Section: Discussionsupporting
confidence: 91%
“…Distinct microbial signatures were identified, with the prevalence of specific OTUs in COVID-19 patients and a particular abundance of Prevotella in severe cases. This was similar to findings from a recent study [30] which highlighted a protective role of the Prevotella genus in the long-term recovery process while other investigations [31,32] reported varied results. The variation could be attributed to various factors like sample collection methods, patient demographics, or even geographic variations in microbial populations.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, it has been reported that there was no significant difference in the expression of bifidobacterial abundance in patients with COVID-19, with the exception of those in the ICU ( 43 ). Furthermore, no differences in probiotic abundance were found at any stage of the viral infection ( 44 ). A study conducted on a European population also demonstrated an increased expression of bifidobacterial abundance in individuals infected with SARS-CoV-2 ( 45 ).…”
Section: Discussionmentioning
confidence: 98%